2022
DOI: 10.3389/fpubh.2022.910675
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Ferroptosis Regulatory Network and Bone Remodeling in Osteoporosis

Abstract: Ferroptosis was induced the programmed cell death with iron overload Fenton reaction. Currently, ferroptosis has not been studied thoroughly. Existing studies have confirmed that ferroptosis involves the metabolisms of the Fe, lipids, amino acid, each mechanism is mutually independent but interrelated, and they are formed a complex regulatory network. Other evidence supports that ferroptosis is participated osteoporotic bone remodeling, predominantly affecting the interaction between bone formation and bone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Many studies have shown that abnormal cell death of osteocytes is involved in the occurrence and development of orthopedic diseases, including bone marrow injury, osteoporosis, osteoarthritis and osteosarcoma. [45,46] Our findings support the concept that osteocytic ferroptosis plays an important role in the maintenance of bone homeostasis. In the mice after bilateral ovariectomy, after GPX4 was knocked out, severe ferroptosis occurred in the osteocytes, while the bone mass of the mice further decreased, and the bone microstructure further deteriorated, indicating that ferroptosis of the osteocytes promoted bone loss.…”
Section: Discussionsupporting
confidence: 83%
“…Many studies have shown that abnormal cell death of osteocytes is involved in the occurrence and development of orthopedic diseases, including bone marrow injury, osteoporosis, osteoarthritis and osteosarcoma. [45,46] Our findings support the concept that osteocytic ferroptosis plays an important role in the maintenance of bone homeostasis. In the mice after bilateral ovariectomy, after GPX4 was knocked out, severe ferroptosis occurred in the osteocytes, while the bone mass of the mice further decreased, and the bone microstructure further deteriorated, indicating that ferroptosis of the osteocytes promoted bone loss.…”
Section: Discussionsupporting
confidence: 83%
“…Several factors have been demonstrated to contribute to the development of osteoporosis, such as inflammatory response, metabolic disorders, and genetic conditions (Ebeling et al, 2022). A few recent studies have established the involvement of ferroptosis in the progression of osteoporosis and the disruption of the balance between osteoclastic and osteogenic activities (Liu et al, 2022b;Gao et al, 2022;Yan et al, 2022). Another report showed that dexamethasone could weaken the activity of intracellular antioxidant systems through downregulation of the SLC7A11/ GPX4 signaling, thereby enhancing the ferroptosis sensitivity of MC3T3-E1 and MOLY4 preosteoblasts and contributing to glucocorticoid-induced osteonecrosis (Sun et al, 2022).…”
Section: Osteoporosismentioning
confidence: 99%
“…The system xc ‐ ‐GSH‐GPX4 pathway dysregulation and iron overload are the main ferroptosis‐initiating factors 16 . Growing evidence has confirmed the vital role of ferroptosis in the maintenance of bone homeostasis 17 . Ferroptosis of osteoporotic target cells including osteoblasts and osteocytes is proposed as the novel and potential mechanism of osteoporosis 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Growing evidence has confirmed the vital role of ferroptosis in the maintenance of bone homeostasis. 17 Ferroptosis of osteoporotic target cells including osteoblasts and osteocytes is proposed as the novel and potential mechanism of osteoporosis. 18,19 Serum from osteoporotic patients is found to induce ferroptosis of osteoblasts thus inhibiting osteogenic differentiation and mineralization.…”
Section: Introductionmentioning
confidence: 99%